Impact Of Publisher\'s Brand Identity On The Sales Of Management Books In Iran - Moshfeghi, Nazli (2010)
This sudy as an eplanatory research tries to scrutinize the relationship between the publisher\'s brand identity and sales of management books in Iran. In the current study, the impact of each construct as an explanatory variable on the sales as the response variable in terms of number of books sold in one year is investigated. The outcome of this study is useful lead to managers and marketing executive of publication industry to pay careful attention to brand identity debvelopment.